2019
DOI: 10.1021/acs.orglett.9b03737
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Substituted Bullvalenes

Abstract: Substituted bullvalenes are dynamic shape-shifting molecules that exist within complex reaction networks. Herein, we report the synthesis of di-and trisubstituted bullvalenes and investigate their dynamic properties. Trisubstituted bullvalenes share a common major isomer which shows kinetic metastability. A survey of the thermodynamic and kinetic landscapes through computational analysis together with kinetic simulation provides a map of the internal dynamics of these systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…While this article was under review, Fallon reported the successful application of this protocol to prepare trisubstituted BV derivatives. 20 Trisubstituted analogues of 1 are prepared in overall yields of 24-50% using trimethylsilylcyclooctatetraene in place of cyclooctatetraene.…”
Section: Complex Fluxional Milieuxmentioning
confidence: 99%
See 2 more Smart Citations
“…While this article was under review, Fallon reported the successful application of this protocol to prepare trisubstituted BV derivatives. 20 Trisubstituted analogues of 1 are prepared in overall yields of 24-50% using trimethylsilylcyclooctatetraene in place of cyclooctatetraene.…”
Section: Complex Fluxional Milieuxmentioning
confidence: 99%
“…Fallon et al built upon this isomer coding system for the network analysis of BV derivatives by developing an algorithm that integrates it with quantum-chemical energy calculations. 9,20 The algorithm generates all the possible BV structures in the dynamic network, identifying enantiomeric pairs and interconnections (i.e., transition states 11 ) between isomers. The geometry of each isomer is then optimised and their single-point energies are calculated through the ORCA 4.0 programme package, 21 forecasting the equilibrium distribution of isomers.…”
Section: Complex Fluxional Milieuxmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The origin of this kinetic feature was explored in a recent study by our laboratory and traced to high barriers in the first and second generation isomerisation from isomer A. 23 DFT analysis and kinetic modelling of triphenylbullvalene predict an isomer A half-life of 4.5 min (see SI for full details).…”
Section: Steps 4-steps Further Substitutionmentioning
confidence: 99%
“…Thus, the reaction appears to be uxional/shape-shiing at room temperature. [36][37][38][39][40] For this substrate, we also modelled the dissociative pathway (Scheme 2D). It was found that bond breakage to two allylic radical intermediates is a higher energy process than the concerted transition state (Scheme 2C vs. Scheme 2D).…”
mentioning
confidence: 99%